Multiple smooth muscle hamartoma: Case report and review of the literature - Haydeh Ghaninezhadh; Massoud Asgary; Pedram Noormohammadpour (Wolters Kluwer Medknow Publications, 2009)
Smooth muscle hamartoma (SMH) is a proliferative disorder of cells originating from muscle cells. It is a benign tumoral mass that usually presents as a single congenital skin-colored and hypertrichotic plaque involving the trunk and extremities. Multiple SMHs have rarely been reported in the literature. We describe the case of a seven-month-old girl with multiple SMHs located over the back and arm areas. The diagnosis was confirmed by biopsy and immunohistochemical (IHC) staining. She had no cerebral or skeletal abnormalities and her growth and development were normal.